Proceedings of the 57th Annual Meeting of the Association for Computational Linguistics 2019
DOI: 10.18653/v1/p19-1422
|View full text |Cite
|
Sign up to set email alerts
|

Towards Near-imperceptible Steganographic Text

Abstract: We show that the imperceptibility of several existing linguistic steganographic systems (Fang et al., 2017;Yang et al., 2018) relies on implicit assumptions on statistical behaviors of fluent text. We formally analyze them and empirically evaluate these assumptions. Furthermore, based on these observations, we propose an encoding algorithm called patient-Huffman with improved near-imperceptible guarantees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…We found that 1.41% of the masked tokens had substitution candidates that did not reproduce the original segmentations. Although this danger applies equally to generation-based steganography built on top of subword LMs (Dai and Cai, 2019;Ziegler et al, 2019;Shen et al, 2020), to our knowledge, we are the first to point it out.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…We found that 1.41% of the masked tokens had substitution candidates that did not reproduce the original segmentations. Although this danger applies equally to generation-based steganography built on top of subword LMs (Dai and Cai, 2019;Ziegler et al, 2019;Shen et al, 2020), to our knowledge, we are the first to point it out.…”
Section: Resultsmentioning
confidence: 96%
“…Let n be the largest integer that satisfies 2 n ≤ c, where c is the number of the remaining items. Each item is given a unique bit chunk of size n. Coding is an active research topic (Dai and Cai, 2019;Ziegler et al, 2019;Shen et al, 2020) and is orthogonal to our core proposal.…”
Section: Encoding Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Then they took the token which has the same code as the secret information. Dai and Cai (2019) proposed patient-Huffman, which was an improved version of Yang et al (2018a) that sacrificed embedding capacity for imperceptibility. They first calculated the distortion (total variation distance or KL divergence) between q and p LM and then only used Huffman coding embedding algorithm to embed secret information when the distortion was less than a preset threshold δ.…”
Section: Imperceptibilitymentioning
confidence: 99%
“…In recent years, powered by the advanced technology of deep learning and natural language processing, language models based on neural networks have made significant progress in generating fluent text (Radford et al, 2019;Brown et al, 2020), which bring new vitality to linguistic steganography and facilitate the investigation of generationbased methods (Fang et al, 2017;Yang et al, 2018a;Dai and Cai, 2019;Ziegler et al, 2019;Yang et al, 2020a;Zhou et al, 2021). The generative linguistic steganography directly transform secret information into innocuous-looking steganographic text (stegotext) without any covertext.…”
Section: Introductionmentioning
confidence: 99%